Analysis of uncorrected near visual acuity after extended depth-of-focus AcrySof® Vivity™ intraocular lens implantation. - Sohee Jeon; Ayoung Choi; Hyunggoo Kwon (PLoS ONE, 2022)
A newly developed extended-depth-of-focus AcrySof® Vivity™ intraocular lens (IOL), which has a wavefront-shaped anterior surface, has shown a promising outcome in minimizing dysphotopsia, the biggest issue after diffractive type IOL implantation. On the contrary, relatively low uncorrected near visual acuity (UNVA) has been raised as a demerit of this IOL. However, there is only limited information about the UNVA after Vivity implantation. In the present study, we compared the uncorrected distant and intermediate visual acuity (UDVA and UIVA) and UNVA according to the range of refractive error (RE) from 91 eyes from 91 patients implanted with Vivity IOL. Then we assessed the biometric factors for their association with UNVA from 66 eyes with a RE within ± 0.25 D. The UDVA was worst in eyes with RE < -0.50 D (0.17 ± 0.21), which was significantly worse than in any other group (P < 0.001 for every analysis). The UIVA was worst in eyes with RE of 0.25 to 0.50 D (0.35 ± 0.07 D), which was significantly worse than in eyes with RE of -0.50 to -0.26 D (P = 0.020) and in eyes with RE of -0.25 to -0.01 D (P = 0.028). The UNVA was worst in eyes with RE of 0.25 to 0.50 D (0.40 ± 0.14 D), which was significantly worse than in eyes with RE of -0.50 to -0.26 D (P = 0.022), which suggests that the extent of monovision should be limited up to -0.50 diopter. On univariate analysis for UNVA in eyes with a RE within ± 0.25 D, the anterior chamber depth (R = 0.257; P = 0.037) and pupil size (R = 0.451; P < 0.001) had a statistically significant relation to UNVA, while multivariate analysis showed the pupil size (β = 0.451; P < 0.001) as the sole indicator, suggesting eyes with a small pupil size might receive a UNVA benefit.